2021 IEEE Electrical Insulation Conference (EIC) 2021
DOI: 10.1109/eic49891.2021.9611381
|View full text |Cite
|
Sign up to set email alerts
|

Partial Discharge Inception Voltage: Precise and Robust Numerical Estimation Based on Extensive Dielectric Spectroscopy Measurements

Abstract: This paper provides a robust experimentalsimulation approach in predicting the partial discharge inception voltage (PDIV) for aeronautical applications. First, two polymers used as insulators in aeronautic components have been selected in this work, a polyimide and a polyetheretherketone. To study the electrical behavior of these materials, extensive dielectric spectroscopy measurements are carried out for different electric fields, temperatures and frequencies (E, T, and f). Then, a needleplane configuration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…This software uses the electric field and electric potential calculated in COMSOL as inputs, and then estimates the PDIV for a given set of environmental parameters based on Paschen's law established from Townsend's theory where g is a parameter that can be modified. The approach presented in [8] showed that PDIV prediction with AIRLIFT is quite robust in this needle-plane configuration. In that case, a maximum deviation under 5 % between the average experimental and computed PDIV was found for a polyimide sample using a value of g = 4.8x10 -4 found by P. Collin et al [3].…”
Section: Airlift and G Estimationmentioning
confidence: 92%
See 3 more Smart Citations
“…This software uses the electric field and electric potential calculated in COMSOL as inputs, and then estimates the PDIV for a given set of environmental parameters based on Paschen's law established from Townsend's theory where g is a parameter that can be modified. The approach presented in [8] showed that PDIV prediction with AIRLIFT is quite robust in this needle-plane configuration. In that case, a maximum deviation under 5 % between the average experimental and computed PDIV was found for a polyimide sample using a value of g = 4.8x10 -4 found by P. Collin et al [3].…”
Section: Airlift and G Estimationmentioning
confidence: 92%
“…C. FEM Simulation The potential and the electric field lines were computed for the same needle-plane configuration described previously thanks to COMSOL Multiphysics ® (5.5). The implementation of the model using the AC/DC module of COMSOL (Electric current) in addition to the chosen meshing strategy in 2D axisymmetric format are described in a previous paper [8]. For instance, Fig.…”
Section: B Pdiv Measurementsmentioning
confidence: 99%
See 2 more Smart Citations